2009
DOI: 10.1103/physrevd.80.105009
|View full text |Cite|
|
Sign up to set email alerts
|

Constraining nonstandard neutrino-quark interactions with solar, reactor, and accelerator data

Abstract: We present a reanalysis of nonstandard neutrino-down-quark interactions of electron and tau neutrinos using solar, reactor and accelerator data. In addition updating the analysis by including new solar data from SNO phase III and Borexino, as well as new KamLAND data and solar fluxes, a key role is played in our analysis by the combination of these results with the CHARM data. The latter allows us to better constrain the axial and axial-vector electron and tau-neutrino nonstandard interaction parameters charac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Recent studies show that this new solution survives combining all the available data on oscillation [6]. In fact in presence of Non-Standard Interactions (NSI), the fit to solar data is slightly better as in the presence of NSI, the upturn of the spectrum at low energy predicted by the standard LMA solution without NSI can be suppressed, leading to a better agreement with the data [3][4][5]. The NSI can also affect other observable quantities such as the invisible decay width of the Z boson (at one-loop) or neutrino scattering off…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Recent studies show that this new solution survives combining all the available data on oscillation [6]. In fact in presence of Non-Standard Interactions (NSI), the fit to solar data is slightly better as in the presence of NSI, the upturn of the spectrum at low energy predicted by the standard LMA solution without NSI can be suppressed, leading to a better agreement with the data [3][4][5]. The NSI can also affect other observable quantities such as the invisible decay width of the Z boson (at one-loop) or neutrino scattering off…”
Section: Introductionsupporting
confidence: 62%
“…Effects of Lagrangian (1.1) on neutrino oscillation have been extensively studied in the literature. In particular in [3][4][5], it is shown that in the presence of a deviation from universality (i.e., | f ee − f µµ |, | f ee − f τ τ | = 0 with f = u, d), another solution with cos(2θ 12 ) < 0 for solar and KamLAND data exists. This solution is known as LMA-Dark solution.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in Refs. [5,[10][11][12], non-oscillation data (such as that from neutrino scattering experiments) is needed to break this degeneracy.Recently, coherent neutrino-nucleus scattering has been observed for the first time by the COHERENT experiment [13], using neutrinos produced at the Spallation Neutron Source (SNS) in Oak Ridge National Laboratory. The observed interaction rate is in good agreement with the Standard Model (SM) prediction and can be used to constrain NSI.…”
mentioning
confidence: 99%
“…As discussed in Refs. [5,[10][11][12], non-oscillation data (such as that from neutrino scattering experiments) is needed to break this degeneracy.…”
mentioning
confidence: 99%
“…[11,[25][26][27][28], both flavor-diagonal and flavor-changing NSI parameters are constrained by neutrino oscillation experiments. They can affect neutrino production, detection, and propagation through matter.…”
Section: Neutrino Oscillationsmentioning
confidence: 99%